UJI EFEKTIVITAS EKSTRAK KULIT JERUK NIPIS (Citrus aurantifolia) TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli DALAM SEDIAAN GEL HAND SANITIZER - Iwang Davi Setiawan; Ade Maria Ulfa; Selvi Marcellia; Indah Aprianti; Artha Meithia; Arta Arum Cahyani (Jurnal Analis Farmasi, 2026)
Hand sanitizer gel has been commonly used as on of the ways to maintain health and hand sanity which is practical and easy to carry along. One of the plant whichi has an anti-bacteria is lime (Citrus aurantifolia). The purpose of this study was to acknowledge lime peel extract's resistance inside a hand sanitizer gel toinhibit the growth od Staphylococcus aureus dan Escherichia coli. The lime peel extraction used maceration method with 96% ethanol solvent. Bacterial inhibition testing on lime peel extract used by the disk method and on hand sanitizer gel preparations used by the wells method. The concentration of lime peel extract used was 20%, 25%, 30%, 35%, 40% and positive control with an average inhibition zone of 8.91 mm, 10.19 mm, 10.42 mm, 10.67 mm , 11.00 mm, 29.16 mm against Staphylococcus aueurus bacteria and 6.89 mm, 8.39 mm, 9.31 mm, 9.72 mm, 9.97 mm and 24.22 mm against Escherichia coli bacteria. In the preparation of hand gel sanitizer, the concentrations used were 20%, 22%, 25% and positive control with an average inhibition zone of 9.11 mm, 9.42 mm, 10.23 mm, 10.40 mm against Staphylococcus aueurus bacteria and 7.21 mm, 8.11 mm, 8.50 mm and 10.35 mm against Escherichia coli bacteria. The antibacterial test results were analyzed using ANOVA, the results of statistical analysis on lime peel extract and hand sanitizer gel of lime peel extract showed a significant inhibition zone difference 0,000 (P = 0.05) between all concentrations of lime peel extract. Lime peel extract in a hand sanitizer gel was effective in inhibiting the bacteria Staphylococcus aureus and Escherichia coli.